Pengaruh Customer Experience dan Customer Value terhadap Loyalitas Pelanggan pada Raja Grosir Kota Bima - Yusnia Ayusari; Ismunandar; Sri Ernawati (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Competition in the retail sector requires companies to optimize customer experience and customer value to maintain customer loyalty. This research applied a quantitative approach with multiple linear regression to examine the influence of these two variables on customer loyalty at Raja Grosir Kota Bima. The sample consisted of 96 respondents selected through purposive sampling, and data were collected using a Likert-scale questionnaire. The findings reveal that both customer experience and customer value have a positive and significant effect on customer loyalty, both individually and simultaneously. The coefficient of determination (R²) value of 0.741 indicates that these variables explain 74.1% of the variation in customer loyalty, with the remainder influenced by other factors outside the model. These results highlight the importance of an integrated strategy that combines enhancing customer experience with perceived value to foster long-term loyalty in the local retail sector.